THE TECHNIQUES BY TEACHERS IN PRESENTING THE MEANING OF NEW VOCABULARY AND THEIR EFFECTIVENESS AS PERCEIVED BY STUDENTS OF THE STRATEGIC MISSION PROGRAM IN VIETNAM NATIONAL UNIVERSITY - Nguyễn, Vũ Xuân Lan (2020)
Strategic Mission is a short name for the project of building and developing 16 branches, 23 specialties of basic science, high technology, economy-society with international standard at Vietnam National University. Students who have not been qualified enough in English to take courses of their major will take a supplement course on language for one year. Due to its young age, it is unavoidable for the project as well as the English course which is applied to encounter numbers of problem and difficulties that need to be studied and adjusted. This study was carried out in order to investigate the techniques of presenting the meaning of new vocabularies by teachers and their effectiveness as perceived by students of the Strategic Mission Project in VNU. Quantitative methods with questionnaire and individual interview were applied to find out the usage of techniques as perceived by both teachers and students, and measure their effectiveness according to the opinion of students from three classes.